Ethical considerations and potential threats to validity for three methods commonly used to collect geographic information in studies among people who use drugs. (October 2016) - Rudolph, Abby E.; Bazzi, Angela Robertson; Fish, Sue
Abstract: Background: Analyses with geographic data can be used to identify "hot spots" and "health service deserts", examine associations between proximity to services and their use, and link contextual factors with individual-level data to better understand how environmental factors influence behaviors. Technological advancements in methods for collecting this information can improve the accuracy of contextually-relevant information; however, they have outpaced the development of ethical standards and guidance, particularly for research involving populations engaging in illicit/stigmatized behaviors. Thematic analysis identified ethical considerations for collecting geographic data using different methods and the extent to which these concerns could influence study compliance and data validity. Methods: In-depth interviews with 15 Baltimore residents (6 recruited via flyers and 9 via peer-referral) reporting recent drug use explored comfort with and ethics of three methods for collecting geographic information: (1) surveys collecting self-reported addresses/cross-streets, (2) surveys using web-based maps to find/confirm locations, and (3) geographical momentary assessments (GMA), which collect spatiotemporally referenced behavioral data. Results: Survey methods for collecting geographic data (i.e., addresses/cross-streets and web-based maps) were generally acceptable; however, participants raised confidentiality concerns regarding exact addresses for illicit/stigmatized behaviors. Concerns specific to GMA included burden of carrying/safeguarding phones and responding to survey prompts, confidentiality, discomfort with being tracked, and noncompliance with study procedures. Overall, many felt that confidentiality concerns could influence the accuracy of location information collected for sensitive behaviors and study compliance. Conclusions: Concerns raised by participants could result in differential study participation and/or study compliance and questionable accuracy/validity of location data for sensitive behaviors. Highlights: Qualitative study of ethical concerns for collecting location data via 3 methods. Confidentiality of illicit behavior locations may influence location data accuracy. Geographical momentary assessments (GMA) collect real-time behavior/location data. GMA concerns included study burden, confidentiality, and discomfort with tracking. GMA concerns could lead to nonparticipation and noncompliance with study procedures.